ALOKASI TENAGA KERJA WANITA PADA USAHATANI PADI UNGGUL VARIETAS CIHERANG DI LAHAN LEBAK KECAMATAN BABIRIK KABUPATEN HULU SUNGAI UTARA - Suslinawati . (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The purpose of this research is: (a) alocation women labour’s in paddy farming Ciherang variety in lebak swampland; and (b) The factors which influence women labour. The result of this research showed that the allocation outpouring women labour in paddy farming Ciherang variety is about 38,09 % from the total farming. Women labour’s who work mostly in the paddy plant is in phase cultivating, raising and harvesting. Cultivating and harvesting phase is an urgent phase of the need of labour. Factors which influence outpouring women labour is due to exprience of farm operation, the large of land ownership; the amount of employment family and the unemployed family. Keywords: Women labour, Paddy farming, Lebak swampland, Ciherang variety